The Effects of personal finance fintech Utilization on generation z's personal financial management - Saffanah, Nurina; Fitri, Denisa Yeli (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
The advancement of digital technology has significantly influenced various aspects of life, including personal financial management. Generation Z, known for its strong affinity with technology, actively uses a variety of digital financial applications such as e-wallets and financial planning platforms. This study aims to examine the extent to which the use of financial applications affects financial management behavior among Gen Z individuals residing in Jakarta. A quantitative approach was employed, using a descriptive method and data collection through questionnaires. The sample was selected purposively, consisting of individuals aged 18 to 24 years. Data analysis was conducted using the SEM-PLS model. The results show that the use of financial applications has a positive and significant influence on financial management behavior, as evidenced by a coefficient value of 0.662. The instruments used have been proven to be valid and reliable, while the analysis model demonstrates a moderate level of predictive capability. In conclusion, financial applications not only serve as technical tools but also help enhance financial understanding and improve financial management habits. These findings are expected to serve as valuable input for app developers, the government, and educational institutions in designing strategies to improve digital financial literacy among the younger generation.